Pengembangan Pendidikan IPS Pada Sekolah Dasar - Dianta, Ahmad; Irnawati, Enka; Priyanto, Sri; Sudrajat, Yayan (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2023)
Social sciences at the school level is basically aimed to prepare students as citizens who master knowledge, skills, attitudes and values , that can be used as an ability to make decisions and participate in various community activities in order to become good citizens. To achieve these objectives, this paper discusses the development of teaching social studies in elementary education, which consists of: 1) recognize the concepts associated with society and the environment, 2) have the basic ability to think logically and critically, curiosity, inquiry, problem solving, and social skills in life, and 3) a commitment and awareness of social values and humanity, 4) have the ability to communicate, cooperate and competation in a pluralistic society, locally, nationally and globally.